PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN WAJIB PAJAK PADA KANTOR PELAYANAN PAJAK PRATAMA GRESIK SELATAN - Elan, Umi; Prayogi, M Restu (Fakultas Ekonomi Universitas Gresik, 2012)
In the socio-cultural life of poor service delivery can lead to disruption of the psychology of taxpayers who indicated the reduced sense of mutual respect, the emergence of mutual suspicion that ultimately lead to taxpayer indifference both to government and to others. Due to a very bad look through a variety of unrest and anarchy in many areas. Along with that taxpayers tend to pick shortcut that leads towards the negative with a range of measures that tend to violate the law. Various problems were identified that appear to be immediately addressed to the taxpayer against the government’s confidence can be restored. The study was done in order to determine the strength of the relationship between service quality to satisfaction of mandatory taxes and to find out how much influence the quality of service to the satisfaction of compulsory taxes.This study uses a quantitative approach to research by the population of taxpayers registered during the month of June 2011 total of 600 taxpayers. While the sampling method used was simple random sampling, the sampling method is random / random and every taxpayer shall have the same opportunity to be sampel.Kesimpulan interpretation of results based on calculations using the statistical F test and t test statistics in the interpretation results indicate that the independent variable quality of service (X) has a significant influence on the dependent variable satisfaction of the taxpayer (Y). Thus the second research hypothesis is proven. Obtained from the SPSS output Coefficientsa simple linear regression model Y = 1.347 + 0.541 X, it means: 1). Constants of 1.347 states that if the quality of service (X) is considered constant (0), then the satisfaction of the taxpayer (Y) = 1.347 for the unit; 2). Regression coefficient of quality of service (X) of 0.541 states that every increase of one unit of service quality (X) will increase taxpayer satisfaction (Y) of 0.541 units.